META ANALISIS: PENGARUH PEMBELAJARAN BERBASIS ETNOMATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Muhammad Turmuzi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The aim of this study is to re-examine the impact of ethnomathematics-based learning on student learning outcomes in mathematics by examining, summarizing data, and statistically assessing various research findings that have been published in up to 18 articles on Google Scholar. This kind of study falls under the category of meta-analysis. Data gathering, coding, calculation of improved student learning outcomes and effect size, detection of average difference existence or absence, and conclusion drawing are some of the research steps. The average effect size is 2.97, with a very large category, according to the study's findings. According to the paired sample t-test, however, the sig value (2 tailed) = 0.000 = 0.05 indicates that there are variations between the typical learning outcomes of students' mathematics before and after applying ethnomathematics-based learning. It may be inferred from the average impact size and the outcomes of the paired sample t-test that the use of ethnomathematics-based learning influences student learning outcomes in mathematics.